A novel hybrid Huffman coding compression technique for secured condition monitoring of induction machine - Das, Jinia Datta; Chowdhuri, Sumana; Bera, Jitendranath (CIEC : proceedings of the 2014 International Conference on Control, Instrumentation, Energy and Communication : January 31, 2014-February 2, 2014, 2014)
In the era of ICT, condition monitoring of machines and sending the data via communication channel to remote location is the subject of extensive research. As communication technique is involved, the channel capacity and data security have become very important issues. In this work a hybrid data compression technique consisting of DPCM and Huffman coding has been proposed for induction machine remote condition monitoring. In different case studies, a considerable amount of the data compression ratio is achieved and data security is also enhanced to a great extent.